The Source of Life and Other Stories - Bosworth, Beth, 1957- (Book collections on Project MUSE., 2012)
"From "The Eight Rhetorical Mode" Later he asked, "Would you like to go for a hike sometime?" and two trains of thought left the station: He means to get to know me and we might leave the city together and it's been a long time since I climbed a mountain. That train chugged into a wider brighter country all the time. The other train went by another route through the panicked interior. He's a lunatic, it whistled. He's been in and out of hospitals. He will take you to a mountaintop and throw you right off into the bright air: choo choo! Post-divorce dating is one more cause for celebration (or a quick call in to the police) in Beth Bosworth's revelatory new book, The Source of Life and Other Stories. The spine of this collection is a series of linked stories about Ruth Stein, a Brooklyn author whose first book has exposed her father's abuses; while the voice here, speaking across a lifetime, ranges from bittersweet to humorous to lethal. In other stories Bosworth's.